TRAIT-BASED STUDIES ON THE ABUNDANCE AND CANOPY SHADE PREFERENCES OF ASTERACEAE SPECIES IN CIBODAS BOTANICAL GARDEN - Decky Indrawan Junaedi; Najwa Wafiyah Az Zahra; Andi Salamah (LPPM Universitas Negeri Jakarta, 2019)
ABSTRACT Knowledge of community structures and capacity to differentiate invasive from non-invasive species are essential for invasive species management. Specific Leaf Area (SLA) is a potential proxy to differentiate invasive from non-invasive species. This study aims to identify the relationship between Important Value Index (IVI) with SLA of Asteraceae species, and predict Asteraceae habitat preference based on shade characteristics at the Cibodas Botanical Garden. There is a positive correlation between SLA and IVI value of Asteraceae species in shaded habitat. The Asteraceae species that prefer shaded habitat tend to have larger SLA relative to species in open area (odds ratio = 2.754). This study showed that SLA is a potential proxy to indicate plant abundance and an informative proxy to predict habitat preferences in CBG ecosystem. These traits information are crucial for invasive exotic plant species management in CBG particularly and tropical botanic gardens in general. Keywords: invasive species, exotic species, SLA, logistic regression, trait, Cibodas, Asteraceae